2020
DOI: 10.3390/en13061362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Prevention of Rockburst in Steeply Inclined and Extremely Thick Coal Seams for Fully Mechanized Top-Coal Caving Mining and Under Gob Filling Conditions

Abstract: The steeply inclined and extremely thick coal seams (SIETCS) under the condition of gob filling frequently suffer from the occurrence of rockbursts. Figuring out the mechanisms of rockbursts under this condition for taking targeted measures to mitigate rockburst hazards in SIETCS is of great significance. Using the typical SIETCS with an average dip angle of 87° at Wudong Coal Mine (WCM) as a case study, a mechanical model and elastic deformation energy (EDE) function of a “steeply inclined suspended roof stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…[8][9][10]. Besides, shallow coals are gradually exhausted; the deep mining geological conditions are more complex; faults, folds, and other geological structures are concentrated, and the development situation of coal resources is extremely severe [11][12][13][14]. e study has shown that the occurrence of coal mine rockburst is closely related to geological structure and other factors; it is easy for rockburst to enter the concentrated burst, especially in the vicinity of faults [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]. Besides, shallow coals are gradually exhausted; the deep mining geological conditions are more complex; faults, folds, and other geological structures are concentrated, and the development situation of coal resources is extremely severe [11][12][13][14]. e study has shown that the occurrence of coal mine rockburst is closely related to geological structure and other factors; it is easy for rockburst to enter the concentrated burst, especially in the vicinity of faults [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] outlined the evolution mechanism of two different types of rock bursts and proposed measures such as caving mining, deep hole blasting, and large diameter drilling, which provided a basis for the risk control of rock burst disasters in subsequent mining activities. He et al [18] studied the mechanism of rock burst in steeply inclined extrathick coal seam and optimized the pressure relief measures by comparing the pressure relief effects of three stress blasting schemes. Cui et al [19] used a physical similar material simulation experiment and acoustic emission monitoring method to study overburden failure law and acoustic emission characteristics in the coal mining process.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [12] studied the failure mechanism of marble under cyclic loading and unloading conditions and provided theoretical basis for rock dynamic disaster prediction. With the development of mining activities, the self-stable state of high stress balance of coal pillar is easily broken by the impact energy formed by the sudden collapse of key strata [13,14]. erefore, the rock burst of coal pillar in overlying coal area is the result of static load and dynamic load [15,16].…”
Section: Introductionmentioning
confidence: 99%